Evaluating the Effectiveness of Mobile Health in Breast Cancer Care: A Systematic Review - Flaucher, Madeleine; Zakreuskaya, Anastasiya; Nissen, Michael; Mocker, Alexander; Fasching, Peter; Beckmann, Matthias; Eskofier, Björn; Leutheuser, Heike (Oncologist, 2023)

Federated electronic health records for the European Health Data Space - Raab, René; Küderle, Arne; Zakreuskaya, Anastasiya; Stern, Ariel D.; Klucken, Jochen; Kaissis, Georgios; Rueckert, Daniel; Boll, Susanne; Eils, Roland; Wagener, Harald; Eskofier, Björn (The Lancet Digital Health, 2023)
The European Commission's draft for the European Health Data Space (EHDS) aims to empower citizens to access their personal health data and share it with physicians and other health-care providers. It further defines procedures for the secondary use of electronic health data for research and development. Although this planned legislation is undoubtedly a step in the right direction, implementation approaches could potentially result in centralised data silos that pose data privacy and security risks for individuals. To address this concern, we propose federated personal health data spaces, a novel architecture for storing, managing, and sharing personal electronic health records that puts citizens at the centre—both conceptually and technologically. The proposed architecture puts citizens in control by storing personal health data on a combination of personal devices rather than in centralised data silos. We describe how this federated architecture fits within the EHDS and can enable the same features as centralised systems while protecting the privacy of citizens. We further argue that increased privacy and control do not contradict the use of electronic health data for research and development. Instead, data sovereignty and transparency encourage active participation in studies and data sharing. This combination of privacy-by-design and transparent, privacy-preserving data sharing can enable health-care leaders to break the privacy-exploitation barrier, which currently limits the secondary use of health data in many case

How Physicians and Patients Interact with Electronic Health Data: A Human-Computer Interaction Perspective - Zakreuskaya, Anastasiya (Frontiers in Artificial Intelligence and Applications, 2023)
The collection and use of personal data is increasing and new developments in Big Data Analytics allow for innovative applications. Recent developments in healthcare, such as the proposal of the European Health Data Space, point towards a more data-driven future of diagnostics and therapy. These developments lead to new challenges, especially in how to design interfaces that support clinicians to navigate through these growing amount of data and new innovative algorithms. Therefore, this work aims to illustrate current experiences of physicians and nurses with health data, investiate possible solutions for data-driven interfaces and ultimately discuss strategies to include new data-sources, such as self-tracking data or patient reported outcome measures.
CRIS-Team Scopus Importer:2023-09-29
Keywords: electronic health records; HCI; health informatics; hospital; interface design; user-centered design

ProgViz: Visualizing Patient Journeys Based on Finite State Models - Zakreuskaya, Anastasiya; Hapfelmeier, Jana (Proceedings of the International Conference on Information Visualisation, 2019)
Patient journeys are the key for treatment development, quality insurance and better understanding of disease progression. Therefore, many visualization toolkits exist to monitor individual patient lives. However, there is no visualization that relies on the overall patterns of patient journeys. We propose a new framework progViz that visualizes patterns of patient journeys, which rely on finite state models. These models are able to illustrate progression of diseases, treatment and outcomes of whole populations as well as very specific analyses. Finally, we propose a method to evaluate how treatment affects disease progression.
Created from Fastlane, Scopus look-up
Keywords: health; medical information systems; patterns; visualization

Your Health, Your Data: Combining Interdisciplinary Views, Concepts, and Practices to Empower Patients in Their Engagement With Personal Health Data - Flaucher, Madeleine; Zakreuskaya, Anastasiya; Jäger, Katharina; Richer, Robert; Smeddinck, Jan David; Kumar, Devender; Grimme, Sophie; Klein, Julia; Hrynyschyn, Robert; Eskofier, Björn; Leutheuser, Heike (Workshopband, 2023)
The collection and use of personal data is increasing and new developments in Big Data Analytics allow for innovative applications. Recent developments in healthcare such as the proposal of the European Health Data Space point towards a more data-driven future of diagnostics and therapy. These developments lead to new challenges, especially in how to design interaction between individuals and their personal health data. With this proposed workshop we want to stimulate discussion about these challenges from the interaction perspective and critically ask, where our health data should lie in the future and who will be owning i